Q. 10

On the basis of t A. z = x + y

B. x = y – z

C. x = y + z

D. y = 2z – x

Answer :


C (graphite) + O2 (g) CO2 (g); ΔrH = x kJ mol–1..…(i)

C (graphite) + O2 (g) CO (g);ΔrH = y kJ mol 1……(ii)

CO (g) + O2 (g) CO2 (g);ΔrH = z kJ mol–1 ……(iii)

Adding (ii) and (iii) will be result in equation (I)

Which means that y + z = x

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses